Identification of modifications in microbial, native tRNA that suppress immunostimulatory activity - Gehrig, Stefanie; Botschen, Flavia; Helm, Mark (Journal of experimental medicine, 2012)
Naturally occurring nucleotide modifications within RNA have been proposed to be structural determinants for innate immune recognition. We tested this hypothesis in the context of native nonself-RNAs. Isolated, fully modified native bacterial transfer RNAs (tRNAs) induced significant secretion of IFN-α from human peripheral blood mononuclear cells in a manner dependent on TLR7 and plasmacytoid dendritic cells. As a notable exception, tRNATyr from Escherichia coli was not immunostimulatory, as were all tested eukaryotic tRNAs. However, the unmodified, 5′-unphosphorylated in vitro transcript of tRNATyr induced IFN-α, thus revealing posttranscriptional modifications as a factor suppressing immunostimulation. Using a molecular surgery approach based on catalytic DNA, a panel of tRNATyr variants featuring differential modification patterns was examined. Out of seven modifications present in this tRNA, 2′-O-methylated Gm18 was identified as necessary and sufficient to suppress immunostimulation. Transplantation of this modification into the scaffold of yeast tRNAPhe also resulted in blocked immunostimulation. Moreover, an RNA preparation of an E. coli trmH mutant that lacks Gm18 2′-O-methyltransferase activity was significantly more stimulatory than the wild-type sample. The experiments identify the single methyl group on the 2′-oxygen of Gm18 as a natural modification in native tRNA that, beyond its primary structural role, has acquired a secondary function as an antagonist of TLR7.
Gesehen am 25.04.2018